Performance and Emission Analysis of Waste Cooking Oil Biodiesel added with Al2O3 Nanoadditive using VCR Engine - et al., Gaikwad Pradeep Uttam (International Journal of Advanced Science and Technology, 2019)
This research work reveals the effect of biodiesel Unsaturation on its fuel properties and thereby on combustion, performance and emissions characteristics. Major part is focused on keeping the compression ration constant at 18 and analyzing different parameters of compression ignition engine. Also added the Al2O3 Nanoadditive in the produced biodiesel.